2011
DOI: 10.1164/rccm.201012-2070oc
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Inhaled Corticosteroids on Outcomes for COPD Patients with Pneumonia

Abstract: Rationale: Treatment with inhaled corticosteroids (ICS) for those with chronic obstructive pulmonary disease (COPD) has been shown to be associated with an increased incidence of pneumonia. However, it is unclear if this is associated with increased mortality. Objectives: The aim of this study was to examine the effects of prior use of ICS on clinical outcomes for patients with COPD hospitalized with pneumonia. Methods: We conducted a retrospective cohort study using the national administrative databases of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 35 publications
3
96
1
1
Order By: Relevance
“…Thus, we cannot discard the possibility that previous administration of ICS is not only a ''marker of COPD'', but that it may reduce lung inflammatory response resulting in fewer pulmonary complications [22]. In concordance with this hypothesis, different authors have clearly suggested that ICS could diminish CAP severity by modulating the local inflammatory response (lung microenvironment and macrophage activation) [23] and subsequent organ dysfunction [24,25] and, possibly, could even reduce mortality rate [26,27]. Our data do not confirm an association of ICS with mortality, but the observed protective effect against pulmonary complications clearly confirms the hypothesis of a positive influence of ICS on CAP severity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot discard the possibility that previous administration of ICS is not only a ''marker of COPD'', but that it may reduce lung inflammatory response resulting in fewer pulmonary complications [22]. In concordance with this hypothesis, different authors have clearly suggested that ICS could diminish CAP severity by modulating the local inflammatory response (lung microenvironment and macrophage activation) [23] and subsequent organ dysfunction [24,25] and, possibly, could even reduce mortality rate [26,27]. Our data do not confirm an association of ICS with mortality, but the observed protective effect against pulmonary complications clearly confirms the hypothesis of a positive influence of ICS on CAP severity.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a study conducted by Dennis Chen et al carried out in south Texas who reported 47.7% of their patients to be smokers. 12 The major clinical complaints of the patients admitted in general medicine were related to Respiratory Tract (59.32%) followed by Dermatological complaints (33.18%), Skeletal (5%), Blood Vessel (0.88%) and Neurological (0.88%) which was similar to study done by SanojVarkey et al in pulmonary department, 13 TP VanStaa et al who conducted the study in general medicine department 14 and a study done in Maharashtra by Wahane Pravin kumar et al who conducted the study in dermatology department. 15 Non-infectious skin diseases like psoriasis topped the Table by 29.33%, followed by Eczema (16%), Pemphigus Vulgaris (8%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of inhaled corticosteroids in COPD patients has been demonstrated to be useful in the reduction of exacerbation events 16,17 and in protection against the development of complicated forms of hospitalized community-acquired pneumonia. 14,15 On the other hand, the long-term use of inhaled corticosteroids increases the risk of pneumonia, [18][19][20] especially with fluticasone. 20 Our study, performed in subjects with COPD exacerbation but without pneumonia, demonstrates that inhaled corticosteroids have no detrimental effect on the development of complications on admission or in other outcomes collected during the clinical course.…”
Section: Discussionmentioning
confidence: 99%